Inter-geosphere interaction in the infrasonic range - Dolgikh, Grigory; Budrin, Sergey; Dolgikh, Stanislav; Chupin, Vladimir; Shvets, Vyacheslav (Frontiers in Earth Science, 2023)
On the basis of experimental data from laser strainmeters, a laser nanobarograph, and a laser meter of hydrosphere pressure variations, we studied inter-geosphere interaction in microseismic range (2-20 s) and in minute range (4-17 min). We established general patterns of transformation of the Earth's crust upper layer oscillations into atmospheric oscillations, and atmospheric oscillationsinto oscillations of the Earth's crust upper layer in the specified ranges. Besides, we show that transformation coefficient has seasonal dependence, associated with different elastic characteristics of the Earth's crust upper layer in winter and summer due to negative winter temperatures and high positive summer temperatures, and also different moisture saturation of the soils.